Documentation of Artefacts in Selected Ghanaian Senior High Schools - Brako-Hiapa, George (2015)
Dissertation Submitted to the School of Graduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the requirements for the degree of DOCTOR OF PHILOSOPHY in Art Education